THE PREVALENCE OF INTEGRON CLASS I AND II AMONG MULTI-DRUG RESISTANCE PRODUCING KLEBSIELLA pneumonia - Omar F. H.; A. H. Ibrahim (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
This study aimed to determine antibiotic resistance profiles and the distribution of Integron I, Integron II, and genes among uropathogenic Klebsiella pneumoniae isolated from patients suffering from urinary tract infection. The results revealed that one hundred and thirty-seven (91%) out of 150 clinical specimens were Klebsiella pneumoniae. The isolates (137 isolates) were given a higher percentage of resistance against Piperacillin (94.89%)and Rifampicin (93.43%) and the lowest resistance was with Meropenem (40.87%). According to PCR amplification for 15 isolates showed the proportion of class I (intl1) and class II (intl2) integrons were investigated. What are 100% (n=15) and 45% (n=7) of isolates had intl1 and intl2 genes, respectively. PCR products for (Five)isolates were subjected to direct sequencing, and both strands of PCR products were sequenced with an automatic sequencer. These sequences were analyzed for the presence of variance of these genes and the detection of the differences in the nucleotides.